ANALYSIS OF BOGOR CITY REGIONAL REGULATION NUMBER 11 OF 2019 ABOUT THE MANAGEMENT AND EMPOWERMENT OF STREET VENDORS - Syafira, Eva Lusiana; Rumatiga, Hidayat; Ilyanawati, R. Yuniar Anisa (Fakultas Hukum Universitas Djuanda, 2024)
The government has issued Bogor City Regional Regulation Number 11 of 2019 concerning the Arrangement and Empowerment of Street Vendors. As we know, the sidewalks on Jalan Merdeka are still filled with street vendors ranging from drink and food sellers and clock repair workers lining the sidewalks along Jalan Merdeka which leads to Red Bridge. As a result of all this, many pedestrians who were walking on the sidewalk had to move to the side of the road, because many street vendors' carts were blocking them. from this research to determine the role, supporting and inhibiting factors as well as the efforts made by the Civil Service Police Unit in controlling street vendors on the sidewalk of Jalan Merdek which leads to Red Bridge. The research used was descriptive qualitative with an inductive approach. Data collection was carried out through interviews, observation and documentation. What is obtained from this research is that the Bogor City Civil Service Police Unit has carried out its role well. The supporting factors for the Bogor City Civil Service Police Unit in controlling street vendors on Jalan Merdeka are having a clear legal basis and good relationships with other agencies. The inhibiting factors include a lack of awareness of street vendors and the community, the absence of clear legal sanctions, limited operational budgets, poor conditions of facilities and infrastructure. The efforts made by the Bogor City Civil Service Police Unit include carrying out additional outreach, maximizing members in every activity, and improving existing facilities and infrastructure.